Review and Development Analysis: The Role of Blockchain Technology in the Halal Food Supply Chain - Muhammad Wahyu Setya Kurniawan; Hana Catur Wahyuni (Journal of Halal Lifestyle and Sustainability, 2025)
This study aims to analyze the priority of integrating the halal supply chain in halal tourism, the opportunities and challenges faced by business actors, and the impact level of halal tourism on entrepreneurs, surrounding communities, and the government. Halal tourism is a tourism concept that provides services, facilities, and primarily to meet the needs of Muslim travelers. The research findings indicate that the current priority in halal tourism lies in enhancing competitiveness and achieving substantial financial benefits. This study seeks to identify priority factors in the integration of the halal supply chain within the tourism sector, focusing on key elements that support the creation of a sustainable halal tourism ecosystem. The research methodology employs a mixed methods approach, combining quantitative analysis through questionnaires distributed to supply chain actors (business owners, academics, tourists) and qualitative analysis through interviews with stakeholders.